2012
DOI: 10.1186/1475-9276-11-35
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining family planning in Catalonia. Sources of inequity

Abstract: IntroductionIn recent decades, the foreign population in Spain has increased significantly, particularly for Catalonia, an autonomous region of Spain (2.90% in 2000 and 15.95% in 2010) and in particular Girona province (6.18% in 2000 and 21.55% in 2010). Several studies have shown a lower use of family planning methods by immigrants. This same trend is observed in Spain. The objective of this paper is to determine the existence of differences and possible sources of inequity in the use of family planning metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…This will prevent the high dependency burden of childbearing and also help them plan for their retirement. This was contrary to a study in Catalonia [39] where older age was not a factor influencing male involvement in family planning but in another study done in Malaysia, Kuala…”
Section: Discussioncontrasting
confidence: 96%
“…This will prevent the high dependency burden of childbearing and also help them plan for their retirement. This was contrary to a study in Catalonia [39] where older age was not a factor influencing male involvement in family planning but in another study done in Malaysia, Kuala…”
Section: Discussioncontrasting
confidence: 96%
“…Education is essential to increase the use of MCM. Those women with a higher degree were more prone to use MCM, which aligns with several previous studies [ 5 , 6 , 10 , 48 ]. Indeed, those with lower educational level are the most affected by existing inequalities in Peru [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…High-SES women may also have taken advantage more quickly than low-SES women of the new family planning services introduced since 1970 (Saurina et al. 2012 ). Another possible reason for the difference is suggested by a US study, which found that poorer women felt they had less choice over the contraceptive method they use, because some methods were too expensive (Cleland et al.…”
Section: Discussionmentioning
confidence: 99%